Seismic Isolation, Structural Health Monitoring, and Performance Based Seismic Design in Earthquake Engineering Recent Developments - Kasimzade, Azer A.; Şafak, Erdal; Ventura, Carlos E.; Naeim, Farzad; Mukai, Yoichi (Springer International Publishing : Imprint: Springer, 2019)
This book features chapters based on selected presentations from the International Congress on Advanced Earthquake Resistance of Structures, AERS2016, held in Samsun, Turkey, from 24 to 28 October 2016. It covers the latest advances in three widely popular research areas in Earthquake Engineering: Performance-Based Seismic Design, Seismic Isolation Systems, and Structural Health Monitoring. The book shows the vulnerability of high-rise and seismically isolated buildings to long periods of strong ground motions, and proposes new passive and semi-active structural seismic isolation systems to protect against such effects. These systems are validated through real-time hybrid tests on shaking tables. Structural health monitoring systems provide rapid assessment of structural safety after an earthquake and allow preventive measures to be taken, such as shutting down the elevators and gas lines, before damage occurs. Using the vibration data from instrumented tall buildings, the book demonstrates that large, distant earthquakes and surface waves, which are not accounted for in most attenuation equations, can cause long-duration shaking and damage in tall buildings. The overview of the current performance-based design methodologies includes discussions on the design of tall buildings and the reasons common prescriptive code provisions are not sufficient to address the requirements of tall-building design. In addition, the book explains the modelling and acceptance criteria associated with various performance-based design guidelines, and discusses issues such as selection and scaling of ground motion records, soil-foundation-structure interaction, and seismic instrumentation and peer review needs. The book is of interest to a wide range of professionals in earthquake engineering, including designers, researchers, and graduate students.